BJP Vs Opposition Parties on Twitter: A Comparison of Social Media Strategies for Political Mobilisation during 2017 Uttar Pradesh and Gujarat Assembly Elections - Singh, Sanjeev Ratna (International Journal of Advanced Science and Technology, 2019)
Social media came to the forefront of political campaigns in India when Narendra Modiused various platforms during the 2014 Lok Sabha elections. But a lot has changed since then and most mainstream political parties have now adapted to social media, especially Twitter. All the top national, state level parties and their leaders have opened social media accounts including Twitter to interact with users on the social media platform. Twitter is now being prominently used as a tool for political communication in India through which political leaders directly reach out to their voters and supporters. Though Narendra Modi is still the most popular political leader on Twitter by far with over 50 million followers, other top opposition leaders started gaining noticeable traction by 2017. After much introspection and reluctance, the Congress revamped its blueprint for political communication and started using Twitter aggressively to win back voters. It tried to project itself as a viable alternative to BJP on social media. Other regional parties like the Samajwadi Party tried to counter BJP’s social media advantage by embracing platforms like Twitter to renew the connect among their supportersduring the 2017 assembly elections. This paper makes use of latest data mining tools and analyses how Twitter was used as a means for political messaging by BJP, Congress and Samajwadi Party during the 2017 assembly election campaign in the state of Uttar Pradesh and for BJP and Congress in Gujarat. It also studies comparative Twitter data for official handles of Prime Minister Narendra Modi, Congress leader Rahul Gandhi, BJP president Amit Shah, the then chief ministers of Uttar Pradesh and Gujarat along with main handles of Congress, BJP in 2017elections on important metrics like volume of tweets, replies, likes, engagement and their respective target areas. The paper provides a detailed insight into how political parties used Twitter as a tool for communication.